Introduction to Sustainable Infrastructure and Environment at Sangkhom Islam Wittaya School, Thailand - Wa Ode Zulia Prihatini; Andi Hakib; Eva Nunung Husna (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The Community Service Program (PKM) introduces Sustainable Infrastructure and Environmental Awareness to students of Sangkhom Islam Wittaya School, Thailand, through participatory and educational methods. This program aims to raise students' awareness, knowledge, and practical skills in caring for environmental cleanliness and managing natural resources effectively. The participatory approach was carried out through green school concept sessions, waste management practices, energy efficiency, and rainwater utilization. The results indicated a 26% increase in participants' understanding based on pre-test and post-test scores with observable changes in behavior towards maintaining cleanliness and saving energy. Islamic integration values throughout the activities also enhanced participants' spiritual motivation to protect nature as a religious moral responsibility. This program is effective in establishing an environmentally friendly culture at the school which can be applied as a model for sustainable education in different schools or even in Indonesia.